Digital intimate Publics and Social Media: Towards theorising public lives on private platforms - Dobson, Amy; Carah, Nicholas; Robards, Brady (Springer, 2018)
Dobson, Carah and Robards theorise digital intimate publics as spaces of power contestation where the public and private intermingle. They draw on queer and feminist theory to examine the generative political potential of ‘oversharing’, ‘excesses’, and ‘unpredictable intimacies’ on social media. They then cogently chart conceptualisations of digital intimacy as both social capital and labour, arguing for the need for digital cultures scholarship to hold these perspectives together. The ability to attract attention by being intimate online can be converted into other kinds of capital. The doing of intimacy online also doubles as labour in the sense that it produces valuable attention and data. The political challenge, they suggest, is to imagine and cultivate public intimacies where both the relations and performative practices and their infrastructure are publicly held.